Analisis Hubungan Komponen Health Belief Model dengan Perilaku Pengelolaan Sampah Pada Masyarakat Pesisir - Rutu, Putri Ayu; G, Fifi Nirmala; Nurmaladewi (Politeknik Baubau, 2025)
Waste is a significant environmental issue, particularly in coastal areas. This study aims to analyze the relationship between components of the Health Belief Model (HBM) and waste management behavior among coastal communities in Mekar Village, Konawe Regency. This quantitative study utilized a cross-sectional design. A total of 217 respondents were selected using a simple random sampling method. The research variables included perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action as independent variables, and waste management behavior as the dependent variable. Data were collected using questionnaires and analyzed using univariate and bivariate methods. The chi-square test results showed the following values: perceived susceptibility (ρ=0.534), perceived severity (ρ=0.030), perceived benefits (ρ=1.000), perceived barriers (ρ=0.000), and cues to action (ρ=0.000). The findings indicate no significant relationship between perceived susceptibility and perceived benefits with waste management behavior in Mekar Village, Konawe Regency, in 2024. However, there is a significant relationship between perceived severity, perceived barriers, and cues to action with waste management behavior in the community